Transformational Leadership : The Power to Achieve School Effectivenesse - Indra Prasetia, (International Journal of Scientific Research and Management (IJSRM), 2024)
This study aims to identify the characteristics of effecive leadership and it influence on school effectiveness in the era of independent learning. To achieve these objectives, this study used an exploratory sequential mixed method. The initial phase on the research used qualitative methods, then the scond phase developed and subtantiated the initial findings widely using quantitative methods. A purposive sampling of 25 teachers was used to collect qualitative data. In the quantitative phase, a survey was conducted among 304 teachers in 59 public junior high schools in North Sumatra Province, Indonesia. The qualitative and quantitative research findings prove and support that transformational leadership is a force to realize school effectiveness in the era of independent learning. These characteristics of transformational leadership are (1) idealized influence, (2) inspirational motivation, (3) intellectual stimulation, and (4) individualized consideration. The idealized influence variable is the variable that most strongly influences school effectiveness by 41.1%; Individualized conciderance is the second most powerful variable affecting school effectiveness by 38.56%; inspiration motivation is the third most powerful variable affecting school effectiveness at 31.36%; intellectual stimulation is the fourth most powerful variable affecting school effectiveness by 17.22%.